Carbon criminals, climate crimes - Kramer, Ronald C. (Critical issues in crime and society, 2020)
"This was a crime:" climate change as a criminological concern -- "Beyond catastrophic:" the climate crisis, carbon criminals, and fossil capitalism -- "When did they know"? Climate crimes of continued extraction and rising emissions -- "The politics of predatory delay:" climate crimes of political omission and socially organized denial -- "Slowing the rise of the oceans"? Obama's mixed legacy and Trump's climate crimes -- "Blood for oil," Pentagon emissions, and the "politics of the armed lifeboat:" climate crimes of empire -- The "climate swerve:" hope, resistance, and climate justice.